(untitled) - Burkhardt, Joanna M. (Chicago, 2003)
This workbook, tied to the ACRL Standards for Information Literacy, provides hands-on tools for reference and instruction librarians at colleges and community colleges as well as others appointed to teach students how to conduct research and to be literate in the information sea. Each exercise address one or more of the nationally accepted ACRL benchmark standards for information literacy education. The exercises promote conceptual and applied skills via active learning, problem-based learning, and/or resource-based learning. Ready-to-use and easy to modify, these 35 lessons can be used as a full semester course or as a single focused seminar or workshop. Covering the basics of planning, collecting, and evaluating, the workbook exercises show how to access books and bibliographic information as well as periodicals and indexes, in addition to online sources
Keywords: Information literacy,Electronic information resource literacy,Library orientation for college students,Huấn luyện kỹ năng thông tin,Kỹ năng sử dụng nguồn tin điện tử,Hướng dẫn sử dụng thư việ cho sinh viên đại học; Study and teaching (Higher),Study and teaching (Higher),Dạy và học (Đại học),Dạy và học (Đại học)